2023
DOI: 10.1007/s00401-023-02597-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of Parkinson's disease brains reveals disease stage specific gene expression changes

Abstract: Parkinson´s disease (PD) is a progressive neurodegenerative disorder characterized by both motor and non-motor symptoms. Aggravation of symptoms is mirrored by accumulation of protein aggregates mainly composed by alpha-synuclein in different brain regions, called Lewy bodies (LB). Previous studies have identified several molecular mechanisms as autophagy and inflammation playing a role in PD pathogenesis. Increased insights into mechanisms involved in early disease stages and driving the progression of the LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…The consistent detection of differential gene expression of mitochondrial genes and genes that code for proteins in the OxPhos chain is likely to have functional impact, given the strong evidence linking mitochondrial impairment and energy metabolism to PD. This includes mitochondrial effects on progression and pathogenesis of PD models in different organisms ( Briston and Hicks, 2018 ; Ordonez et al, 2018 ; Ikuno et al, 2021 ; Murali Mahadevan et al, 2021 ), the toxic effects of MPTP and Rotenone, a reduced activity of complex I in postmortem PD brains ( Cappelletti et al, 2023 ) and the association between PD genes and mitochondria ( Rekaik et al, 2015a ). In addition, inhibition of the mitochondrial pyruvate carrier has been shown to directly slow down pyruvate oxidation in isolated brain mitochondria, to increase the utilization of other substrates, to normalize oxygen consumption after MPP+ treatment, to reduce dopaminergic neurodegeneration in vitro and in vivo , and well as to reduce motor impairment in OF1- En1 +/− mice ( Ghosh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The consistent detection of differential gene expression of mitochondrial genes and genes that code for proteins in the OxPhos chain is likely to have functional impact, given the strong evidence linking mitochondrial impairment and energy metabolism to PD. This includes mitochondrial effects on progression and pathogenesis of PD models in different organisms ( Briston and Hicks, 2018 ; Ordonez et al, 2018 ; Ikuno et al, 2021 ; Murali Mahadevan et al, 2021 ), the toxic effects of MPTP and Rotenone, a reduced activity of complex I in postmortem PD brains ( Cappelletti et al, 2023 ) and the association between PD genes and mitochondria ( Rekaik et al, 2015a ). In addition, inhibition of the mitochondrial pyruvate carrier has been shown to directly slow down pyruvate oxidation in isolated brain mitochondria, to increase the utilization of other substrates, to normalize oxygen consumption after MPP+ treatment, to reduce dopaminergic neurodegeneration in vitro and in vivo , and well as to reduce motor impairment in OF1- En1 +/− mice ( Ghosh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because existing meta-analyses that have delineated DEGs associated with PD, we curated and compiled PD-DEG sets from three relevant studies [36][37][38] (Table 2). These studies performed metaanalyses of PD transcriptomic data to derive robust gene expression signatures for the disease.…”
Section: Collection Of Degs Through Pdmentioning
confidence: 99%
“…Additionally, PD-associated genes identified through TWAS in the brain tissue were obtained from the TWAS-Atlas database 39 and incorporated. In total, the PD-DEG comprised 2,895 unique genes (1,378 from PMID:27611585 36 , 585 from PMID: 33390883 37 , 989 from PMID: 37347276 38 , and 196 from the TWAS-Atlas) [Figure 2]. Gene set enrichment analysis (GSEA) confirmed the signature of the PD-DEG compilation, with the most enriched term as "has05012: Parkinson disease" [Figure 3a].…”
Section: Collection Of Degs Through Pdmentioning
confidence: 99%
“…Bulk RNA-seq analyses of the midbrain [45], prefrontal cortex [51], and frontal cortex [55] have all identified transcriptional evidence for inflammatory pathways in PD samples. The strongest signal was derived from the midbrain, as bulk RNA-seq disclosed that approximately half of the DEGs between PD samples and non-PD controls were related to the immune-inflammatory response [45].…”
Section: Glial Cells Activate Inflammatory Pathways In Pdmentioning
confidence: 99%
“…In contrast, an activated inflammatory response in the PD prefrontal cortex was inferred by bulk RNA-seq through significant increases in microglia and oligodendrocyte marker gene profiles compared to non-PD controls, without any differential gene expression to suggest an elevated inflammatory response in PD [51]. In the frontal cortex, Cappelletti et al leveraged bulk RNA-seq data from 84 samples, allowing them to maintain power upon stratifying the PD samples into three groups according to their degree of Lewy body pathology-based on the Braak Lewy body stage-which was used as a proxy for disease progression [55]. In doing so, the authors observed that immune response pathways were upregulated at early disease stages and downregulated at the most advanced stage [55].…”
Section: Glial Cells Activate Inflammatory Pathways In Pdmentioning
confidence: 99%